Study on bioactivity of lime, Citrus aurantifolia (Christm.) against larvae of Diamond back moth, Plutella xylostella (L.) on cabbage crop under laboratory condition. - Arani, Y.; Nithiyagowry, R. (University of Jaffna, 2021)
High feeding activity of larval stages of Plutella xylostella leads to reduction in yield and causes economical loss. The uses of plant products are reported to be an alternative to synthetic pesticides for insect pest management. With this background, a laboratory study was carried out to evaluate the lethal, phagodetterent and post embryonic develomental effects of aqueous and methanol leaves extracts of Citrus aurantifolia on the third instar larvae of P.xylostella and compared with a synthetic pesticide Spinosad. Three concentrations of methanol leaf extract (MeLE) ( 0.05g/ml, 0.125g/ml and 0.2g/ml ) , aqueous leaf extract (AqLE) ( 0.05g/ml, 0.15g/ml, and 0.2g/ml) and synthetic pesticide (SynP) (5g/l, 15g/l and 25 g/l) were tested along with solvent controls against 3rd instar larvae of P.xylostella. Larvae fed with cabbage leaves disc treated with MeLE at 0.2g/ml and AqLE at 0.15g/ml significantly (P<0.05) reduced the leaf consumption after 24 hours compared to controls. There was no significant difference (P˃0.05) in leaf consumption between MeLE and AqLE. All the concentrations of MeLE and AqLE showed significantly (P<0.05) higher lethal effects after 48 h of exposure. LD 50 values for MeLE and AqLE were found as 0.123 g/ml and 0.89 g/ml respectively after 48 h of treatment. All concentrations of synthetic pesticide except 5g/l showed 100% larval mortality after 24 hours of treatment. Pupal deformities and abnormal adult with curled wing also observed at 0.2g/mL of MeLE and 0.15 g/ml AqLE respectively. This study revealed that leaf extract of C.aurantifolia caused lethal, phagodetterent and growth inhibitory effect on larvae of P. xylostella..
Keywords: Citrus aurantifolia; Synthetic pesticide; Plutella xylostella; Phagodetterent; Lethal; Growth inhibitory